Piezoelectric cutting devices for osteotomy in Temporomandibular joint condylectomy (2020)
Condylar hyperplasia is an alteration in mandibular growth that can cause facial asymmetry and occlusal changes that usually affect the aesthetics and function of patients. To date, condylectomy for its part remains a key part of the treatment. Although there are still controversies regarding the amount of bone to remove and the surgical approach, there are still other concerns, such as finding the benefit in terms of intraoperative safety and postoperative results with different cutting devices, including the use of piezoelectric, which is increasing its use in the maxillofacial field. This is why the main objective of this study is to compare the results found in medical records and databases of condylectomy procedures performed between 2017 and 2019 with different cutting devices.